Creative ageing in Singapore : a population study on participatory arts engagement and wellbeing among adults aged 50 and above - Ma, Stephanie Hilary Xinyi (Nanyang Technological University, 2020)
While anecdotal and increasing empirical evidence suggest that participatory arts can play an essential role in supporting a healthy ageing population, much less research has been conducted in Asian societies. Furthermore, despite growing interest in arts programmes for older adults in Singapore, little is known about the patterns and impact of arts engagement among local seniors. This thesis presents an analysis of the quantitative data of a larger mixed-methods population research, namely, the ‘Arts for Ageing Well’ study to understand the patterns of arts engagement among Singaporean adults aged 50 and above, to investigate the relationships between participatory arts engagement and holistic wellbeing, as well as to explore the impact that specific art form engagements may have on health and wellness. Adopting a cross-sectional stratified random household survey, 1,067 community-dwelling Singaporean older adults between the ages of 50-95 years were recruited from all residential areas across Singapore. Participants were administered a self-reported questionnaire which evaluated a comprehensive list of active and passive participatory arts engagement. Outcome measures included quality of life, self-rated health, spiritual wellbeing and social support. Control variables included demographic information, self-reported health status, intensity and frequency of physical exercises. Descriptive analyses indicated that passive arts engagement rate was 60% while active arts engagement rate was 17% among older adults aged 50 and above. Respondents expressed that their greatest interest lies within the genre of culture and heritage arts, with a strong preference to engage in arts activities within the community, and to attend such activities with their family or friends. Findings from propensity score matching with t-test analyses revealed that respondents who passively engaged in the arts experienced better quality of life t(728) = 3.35, p = .0008, d = .25, self-perceived health t(728) = 2.21, p = .028, d = 0.16, and sense of belonging t(728) = 2.17, p = .028, d = 0.16, as compared to those who did not. Moreover, participants who actively engaged in the arts experienced enhanced quality of life t(442)= 3.68, p = .0003, d = 0.36, self-perceived health t(442) =2.59, p = .0099, d = 0.25 and spiritual wellbeing t(442) = 3.75, p = .0002, d = 0.37, as compared to non-art active participants. Exploratory t-tests conducted for engagement in specific art form revealed that both passive and active engagements in dance was most beneficial for the wellbeing of the older adults in the study. This research highlights the potential health benefits of arts engagement among community dwelling older adults and provided robust evidence for Asian societies to invest in the arts for health promotion and research. Practice and policy recommendations are discussed.